Students’ Differences, Societal Expectations, and the Discursive Construction of (De)Legitimate Students in Germany - Bernhard, Nadine (Social Inclusion, 2021)
At higher education institutions (HEI), which for centuries served only to educate the elite, the composition of the student body is increasingly changing towards greater social and cultural diversity. Students’ differences are also the focus of this article, but not with a specific emphasis on preselected categories. Instead, the article asks how students in teaching in higher education (HE) are represented in the print media and professional discourse in Germany, i.e., which categories of difference are constructed as relevant in HE teaching contexts, which are normalized and (de)legitimized, and what is expected of HEI concerning these differences. Second, to what extent does this change over time, particularly concerning the new circumstances of Corona‐based digital teaching in 2020? The contribution is based on a combination of discourse theory and neo‐institutional organizational sociology. Discourses are a place where social expectations towards organizations are negotiated and constructed. Simultaneously, the discourses construct a specific understanding of HE, making visible openings and closures concerning different groups of students. Which students are constructed as legitimate, desirable, at risk of dropping out, or a risk for HE quality? Based on qualitative content analysis, the article shows that it is less the traditional socio‐structural categories such as gender, social or ethnic origin, or impairments, that are discussed to be relevant in HE teaching contexts. The reproduction of inequality and the associated discrimination is hardly discussed. The focus is instead on the students’ differences concerning individualizable characteristics, competencies, or study practices. Even though many of these individualized differences are conveyed via socio‐structural categories, this connection is often not considered in the discourses.